Competition in Print Advertising between Paid and Free Newspapers - Lydia Cheung; Geoffrey Brooke (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2018)
This paper looks at the market for print advertising in New Zealand, which is characterized by rich variation in ownership structures of overlapping paid daily metropolitan newspapers and free weekly suburban newspapers. We first present stylized empirical facts on advertising rates and readership shares, from an original dataset. We then present a simple model whose market outcome varies with ownership structure in the same manner as our empirical observation.
Keywords: D12; L11; L13; L41; 330; Newspaper; Print Advertising; Ownership STructure; Competition